The porous high-press? An experimental approach investigating tactical behaviours from two pressing strategies in football - Low, B.; Rein, R.; Raabe, D.; Schwab, S.; Memmert, D. (Journal of Sports Sciences, 2021)
The aim of this study was to analyse footballers` tactical behaviours from their position data, as an effect of two contrasting pressing strategies, high-press defending and deep-defending, using a trial-based experimental approach. Sixty-nine youth footballers participated in this 11 versus 11 study, performing 72 trials of attack versus defence, in a counterbalanced crossover study design. Players` position data were captured using a local positioning system, and processed to calculate measures of inter-team distance, trial duration, distance to nearest opponent, dispersion, team length, team width, team shape, space control gain, inter-line distance, and individual area. This was augmented by the notational analyses of passes. The findings showed that using a high-press defending strategy leads to: closer inter-team distance; larger dispersion, due to a longer team length; and larger inter-line distances between defenders, midfielders, and forwards. The resulting effects on the attacking team include reduced ball possession time; larger individual areas for attacking midfielders and forwards; longer team length; and more penetrative passes performed. Some differences in marking behaviour were also observed. Consequently, the study recommends that high-press defending be used sparingly due to these trade-offs.